Ответ:
-80
Объяснение:
...................
12ab(13a² - b²) + 13ab(b² - 12a²) =
156a³b - 12ab³ + 13ab³ - 156a³b =
(156a³b - 156a³b) + (-12ab³ + 13ab³) =
0 + 1ab³ = ab³
a = 10; b = -2
ab³ = 10 * (-2)³ = 10 * (-8) = -80
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
-80
Объяснение:
...................
Ответ:
-80
Объяснение:
12ab(13a² - b²) + 13ab(b² - 12a²) =
156a³b - 12ab³ + 13ab³ - 156a³b =
(156a³b - 156a³b) + (-12ab³ + 13ab³) =
0 + 1ab³ = ab³
a = 10; b = -2
ab³ = 10 * (-2)³ = 10 * (-8) = -80